Dissecting saving dynamics: measuring wealth, precautionary and credit effects - Christopher Carroll; Jiri Slacalek; Martin Sommer (European Central Bank (ECB), 2012)
We argue that the U.S. personal saving rate's long stability (from the 1960s through the early 1980s), subsequent steady decline (1980s-2007), and recent substantial increase (2008-2011) can all be interpreted using a parsimonious `buffer stock' model of optimal consumption in the presence of labor income uncertainty and credit constraints. Saving in the model is affected by the gap between `target' and actual wealth, with the target wealth determined by credit conditions and uncertainty. An estimated structural version of the model suggests that increased credit availability accounts for most of the saving rate's long-term decline, while fluctuations in net wealth and uncertainty capture the bulk of the business-cycle variation.
Keywords: E21; E32; 330; Consumption; credit availability; saving; uncertainty; wealth